SLEEPING - AN EFFICIENT WAY OF PERFORMANCE SPORTSMEN RECOVERING - Juravle Mariana (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
Sleeping is a brain activity state characterized by temporary interruption of conscient touch with the exterior and interior, being a reverse state. The passing to sleep state and the other way around is made easily, in a few seconds, and wakeful state coincides with night-day cycle, that's why it is also called circadian. During sportsmen spontaneous restoration, profound and resting sleep, which has an important role in the intellectual and physical abilities, will lead to the development of psycho-motile performances during trainings and competitions.